Tell Tale Increasing Skill: Increasing Indonesian Student Reading Comprehension Through Indonesian Folklore - Endang Ernawati; Retnowati Retnowati (Bina Nusantara University, 2016)
The goals of the research were to compile a reading material that was able to measure the fifth year primary students’ comprehension to the Betawi folklore which represented Indonesian culture; the value found in the Betawi folklore, and to increase their writing skills based on the vocabulary in context assessment. A library research was applied by selecting the story suitable for primary school students, translating materials, simplifying the reading, and making reading exercise to develop student’s reading comprehension skills. Reading materials and exercises were focused to the fifth year primary students who have been learning English for more than three years. It can be concluded that the interesting reading materials can be compiled from the original Indonesian folklore entitled “The Old Sly Stork” to support students’ achievement in finding the story’s values, and students’ skills in writing based on the reading materials, value, and their daily life experiences.